Pemahaman Konsep Peserta didik Melalui Penerapan Model Bamboo Dancing - Irma Sofiasyari; Aan Yuliyanto (Jurnal Elementaria Edukasia, 2023)
The background of the research was lack of the learners’ concepts due to not-optimum learning model implementation. This situation did not provide the learnres adequate opportunities to participate in the learning. This research aimed to improve the conceptual understandings of the learners. The subjects consisted of 24 learners: 8 male and 16 female learners. The researchers collected the data with test, observation, field note, and documentation. The techniques of analyizng the data were quantitative analysis for the conceptual understanding of the learners on each cycle and qualitative data analysis on each cycle. The results showed that Baboo Dancing model implementation could improve the fifth graders’ conceptual understanding at Public Primary School Babakanjawa V. The result showed improvements from the pre-cycle stage. The learning accomplishment reached a percentage of 41.66% in pre-cycle. Then, the results improved into 66.66% in cycle I and increased into 87.5% in cycle II. The improvements indicated the implementation of Bamboo Dancing could improve the conceptual understandings of the learners.